GROWTH PERFORMANCE OF BROILER CHICKENS FED DIET CONTAINING GRADED LEVELS OF (Saccharomyces cerevisiae ) SUPPLEMENTATION - Elijah, P.; Akintunde, A. R.; Jude, U.; Danladi, Y.; Yusuf, D.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The experiment evaluated the effects of graded levels of Saccharomyces cerevisiae supplementation on the growth performance and nutrient utilization of broiler chickens. Two hundred (200) day-old broiler chicks were randomly assigned to five dietary treatments: a controldiet (T1) and diets supplemented with 0.50 g (T2), 1.00 g (T3), 1.50 g (T4), and 2.00 g (T5) S. cerevisiae per kilogram of feed in a Completely Randomized Design (CRD). Birds were raised for eight weeks under standard management conditions and fed starter diets for the first four weeks and finisher diets for the remaining period. Performance parameters including feed intake, body weight gain, average daily weight gain, feed conversion ratio (FCR), and mortality were recorded and analyzed. Results indicated that supplementation at 1.00 g/kg (T3) significantly (P< 0.05) improved body weight gain and feed efficiency in both starter and finisher phases compared to control and other treatments (P < 0.05). However, higher supplementation (2.00 g/kg, T5) increased FCR, suggesting reduced efficiency. The findings demonstrate that S. cerevisiae supplementation at 1.00 g/kg optimizes growth performance, feed utilization, and gut health in broiler chickens, offering a viable alternative to antibiotic growth promoters.